2008
DOI: 10.1080/10400410802391835
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Culture on the Creative Potential of American, Russian, and Iranian College Students

Abstract: This study presents evidence for the impact of sociocultural environment on creative potential. The divergent thinking performance of American, Russian, and Iranian college students was compared on the Abbreviated Torrance Test for Adults. The study revealed that, compared to the Iranians, Americans and Russians have superior abilities to consider a problem from different perspectives and to generate original solutions to a problem. The performance differences on the originality measure of the representatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Khaleefa, Erdos, &Ashaia, 1996). This might also explain the findings of Kharkhurin and Motalleebi (2008). They studied creative potential in three different countries--the United…”
Section: Discussionmentioning
confidence: 85%
“…Khaleefa, Erdos, &Ashaia, 1996). This might also explain the findings of Kharkhurin and Motalleebi (2008). They studied creative potential in three different countries--the United…”
Section: Discussionmentioning
confidence: 85%
“…In fact, the instrument has been shown to provide valid, reliable, and objective measures of verbal and figural creativity in adults that correlate with creative performance in the workplace (Althuizen, Wierenga, & Rossiter, 2010;Cramond, Matthews-Morgan, Bandalos, & Zuo, 2005). The instrument has also been employed in a number of different contexts involving adult college students (e.g., Kharkhurin & Samadpour Motalleebi, 2008) and has been shown to provide acceptable levels of reliability and validity with this population as well.…”
Section: Methodsmentioning
confidence: 95%
“…Research has also identified a role of multicultural experience in influencing creative cognition, both in terms of culture of origin influencing creative potential (e.g. Kaufman & Sternberg, 2006;Kharkhurin & Samadpour Motalleebi, 2008;Niu & Sternberg, 2001) and in cultural experience (Maddux & Galinsky, 2009) and cultural priming (Jia, Hirt, & Karpen, 2009) improving creative problem solving. As such, one might argue that the multilingual effects identified in this study may be in part due to differences in multicultural experience between the groups.…”
Section: Discussionmentioning
confidence: 97%